Monetary Reward and Punishment to Response Inhibition Modulate Activation and Synchronization Within the Inhibitory Brain Network - Chikara, Rupesh K.; Chang, Erik C.; Lu, Yi-Chen; Lin, Dar-Shong; Lin, Chin-Teng; Ko, Li-Wei (Frontiers in Human Neuroscience, 2018)
A reward or punishment can modulate motivation and emotions, which in turn affect cognitive processing. The present simultaneous fMRI-EEG study examines neural mechanisms of response inhibition under the influence of a monetary reward or punishment by implementing a modified stop-signal task in a virtual battlefield scenario. The participants were instructed to play as snipers who open fire at a terrorist target but withhold shooting in the presence of a hostage. The participants performed the task under three different feedback conditions in counterbalanced order: a reward condition where each successfully withheld response added a bonus (i.e., positive feedback) to the startup credit, a punishment condition where each failure in stopping deduced a penalty (i.e., negative feedback), and a no feedback condition where response outcome had no consequences and served as a control setting. Behaviorally both reward and punishment conditions led to significantly down-regulated inhibitory function in terms of the critical stop-signal delay. As for the neuroimaging results, increased activities were found for the no feedback condition in regions previously reported to be associated with response inhibition, including the right inferior frontal gyrus and the pre-supplementary motor area. Moreover, higher activation of the lingual gyrus, posterior cingulate gyrus and inferior-parietal lobule were found in the reward condition, while stronger activation of the precuneus gyrus was found in the punishment condition. The positive feedback was also associated with stronger changes of delta, theta and alpha synchronization in the posterior cingulate gyrus than were the negative or no feedback conditions. These findings depicted the intertwining relationship between response inhibition and motivation networks.